Online Education Administration Guidelines for Aviation Management Undergraduates - Moungsawad, Attapol; Sirisombat, Dusit; Mekintharanggur, Khachitpan; Hongsakul, Bharis (Journal of Information and Learning [JIL], 2021)
The purposes of the research were: 1) to study aviation management undergraduates' opinions towards online education administration, 2) to study the relationship between undergraduates' use of digital equipment for online learning and preferred online teaching methods, and 3) to propose the guidelines of online education administration. 464 undergraduates answered questionnaires. The results showed that the majority of the sample felt content by online learning but felt lonely and stressed sometimes; furthermore, they could access and review the study material at their own pace. But, they lacked self-discipline and had more inquiries while studying online. Moreover, they mentioned that lectures assigned too many assignments. The sample had to purchase digital equipment and internet service for online learning. They also stated that they had problems with digital equipment, application, and an internet connection occasionally. According to the survey, the majority of the sample preferred blended online teaching methods. The relationship between undergraduate’s usage of digital equipment for online learning and preferred online teaching methods was significant at the .05 level. Also, the guidelines suggested that lectures should focus on students' diverse backgrounds and implement blended online teaching methods in the online classroom.